Determination of Maintenance Time Interval Scheduling on Jaw Crusher Machine with Reliability Centered Maintenance Method At PT. X In Rembang - Muhyidin Agus Wibowo, Moh; Kalista, Anggia; Suwardana, Hendra; Parayuda, Muhammad Hendriyanto (Journal Knowledge Industrial Engineering (JKIE), 2026)
The manufacturing industry in the construction-support mining sector faces significant challenges in maintaining the reliability of production equipment, particularly in jaw crusher machines used for andesite stone processing. Frequent machine breakdowns during production activities can reduce productivity, increase downtime, and cause financial losses. This study aims to identify critical components and determine optimal maintenance intervals using the Reliability Centered Maintenance (RCM) method. The analysis results indicate that the critical components of the jaw crusher machine are the Bearing, Toggle, Electric Motor, and Spring. The Bearing and Toggle components require corrective maintenance strategies with maintenance intervals of 111 days, while the Electric Motor and Spring components require preventive maintenance strategies with intervals of 119 days and 109 days, respectively. The proposed maintenance scheduling can be used as a basis for improving machine reliability, minimizing downtime, and enhancing maintenance effectiveness in the production process.